The Influence of Game-Based Coding Learning on Creativity in Early Childhood Education - Ibnu Imam Al Ayyubi; Siti Rahmawati (Episteme: Jurnal Kajian Mahasiswa, 2026)
The integration of coding into early childhood education has gained increasing attention as digital literacy becomes an essential competency in the twenty-first century. However, empirical studies examining how game-based coding activities contribute to creativity development among young children remain limited. This study aims to explore how game-based coding instruction influences creativity in early childhood education settings. Using a qualitative case study approach, the research was conducted at TK Wulil Amri, an early childhood education institution that has implemented game-based coding in its learning activities. Participants included children aged 5–6 years, teachers, and parents. Data were collected through in-depth interviews, participatory observations, and document analysis, and analyzed using thematic analysis. The findings indicate that game-based coding activities support children's creative development by encouraging divergent thinking, problem-solving, and exploratory learning behaviors. Children actively experimented with different coding possibilities rather than merely following instructions, demonstrating initiative and imaginative engagement in the learning process. This study contributes to the emerging field of digital learning in early childhood education by highlighting the potential of game-based coding as a pedagogical strategy to foster creativity in young learners. The findings also suggest that developmentally appropriate educational technologies can play an important role in supporting creative learning environments in early childhood education.